Enhancing Corporate Social Responsibility with Blockchain-based Trackable ESG Tokens - Miranda, Yang R.; Alves, Paulo H.; Paskin, Ronnie; Nasser, Rafael B.; Robichez, Gustavo; Faria, Luiz; Trindade, Roberto; Silva, Joana; Peixoto, Leandro; Miranda, Fernando Pellon de (Workshop em Blockchain: Teoria, Tecnologias e Aplicações (WBlockchain), 2023)
ESG is a sustainability framework promoting sustainability and responsible business practices relevant to Petrobras, a major Brazilian oil and gas company. In this sense, blockchain emerged as a technology for trustworthy information storage. This work demonstrates the ESG Token solution, built on top of EVM-compatible smart contracts to address data and process transparency, security, availability, and auditability. RBB (Brazilian Blockchain Network) was used to deploy the ESG Token smart contract, and the pluggable architecture allows for separating the blockchain layer from the business solution. Furthermore, ESG Token integrates with GovBR’s digital signature platform, enabling self-declarations of validated identities to enhance accountability.